2022
DOI: 10.1002/pros.24427
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA profiling for prediction of oncological outcomes in prostate cancer patients following radical prostatectomy

Abstract: Background: Although radical prostatectomy is associated with good long-term oncological outcomes, approximately 30% of patients present biochemical recurrence, whereupon salvage treatments are required. Identification of novel molecular biomarkers to predict cancer behavior is clinically important. Here, we developed a novel microRNA (miRNA)-based prognostic model for patients who underwent radical prostatectomy. Methods: We retrospectively investigated the clinical records of 295 patients who underwent radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…demonstrated that a signature of three miRNAs (miR‐186‐5p, miR‐320a‐3p, and miR‐30e‐5p) from urinary extracellular vesicles is a promising marker for active surveillance 79 . Recently, we also reported that a combination of three plasma miRNAs (miR‐3147, miR‐4513, and miR‐4728‐5p) and two pathological factors (pathological T stage and Gleason score) could be a predictive biomarker for recurrence after prostatectomy 80 . Together with phase 2 and 3 studies, ancillary exploratory analyses were recently performed.…”
Section: The Clinical Significance Of Extracellular Mirnas In Liquid ...mentioning
confidence: 95%
See 1 more Smart Citation
“…demonstrated that a signature of three miRNAs (miR‐186‐5p, miR‐320a‐3p, and miR‐30e‐5p) from urinary extracellular vesicles is a promising marker for active surveillance 79 . Recently, we also reported that a combination of three plasma miRNAs (miR‐3147, miR‐4513, and miR‐4728‐5p) and two pathological factors (pathological T stage and Gleason score) could be a predictive biomarker for recurrence after prostatectomy 80 . Together with phase 2 and 3 studies, ancillary exploratory analyses were recently performed.…”
Section: The Clinical Significance Of Extracellular Mirnas In Liquid ...mentioning
confidence: 95%
“…79 Recently, we also reported that a combination of three plasma miRNAs (miR-3147, miR-4513, and miR-4728-5p) and two pathological factors (pathological T stage and Gleason score) could be a predictive biomarker for recurrence after prostatectomy. 80 Together with phase 2 and 3 studies, ancillary exploratory analyses were recently performed. In the phase 2 SWOG S0925 study, which evaluated the utility of cixutumumab with ADT in metastatic HSPC patients, miR-375 in plasma was a predictor of the 28 week prostate-specific antigen (PSA) response.…”
Section: Prognostic Extracellular Mirnasmentioning
confidence: 99%